A study of grass structure and function in response to drought and grazing - Zaricor, Marissa Lynne (Kansas State University, 2021)
Grass species have variable drought tolerance, which has been shown to contrast among grass lineages and between photosynthetic pathways (C₃,C₄). Knowledge of which structural or functional traits may allow certain grass species from different grass tribes to tolerate severe drought remain limited. In the first half of my thesis, I examined how several grass species responded to drought by measuring leaf-level physiology, and morphological traits of leaves and roots to address: 1) how do leaf-level gas-exchange responses to drought vary among photosynthetic pathways (C₃, C₄) and/or between grass tribes (Andropogoneae, Cynodonteae, Paniceae, and Danthonieae) over a time course of well-watered, to maximum drought, and following recovery? And 2) do morphological traits (e.g., leaf area, root length) vary between grass lineages and/or photosynthetic pathways? I found that grasses using the C₄ photosynthetic pathway were no more resilient than C₃ grasses under severe drought. This work also demonstrated that species from closely related tribes shared common morphological characteristics and displayed similar physiological responses to drought, despite using different photosynthetic pathways, emphasizing the need to include phylogeny in ecophysiological research. The second half of my work, I investigated belowground dynamics in response to grazing of two tallgrass prairie species (Andropogon gerardii and Sorghastrum nutans) from three sites in the Great Plains. Grasses have co-evolved with disturbance (e.g., fire and grazing), resulting in large investments into belowground biomass. Roots and belowground storage organs (e.g., rhizomes) are responsible for acquiring limited resources, carbohydrate storage, and resprouting after disturbances. Grazing has the potential to alter growth of these belowground structures, yet few investigations examine root responses in paired grazed/ungrazed locations or beyond just the superficial depths of the soil profile. Here, I explored how grazing altered grass root and rhizome structure and function by taking soil cores from grazed and ungrazed treatment areas in three native tallgrass prairies, where I compared root traits and non-structural carbohydrates (NSCs) by soil depth. I addressed two main questions: 1) does grazing alter root morphology (e.g., length, diameter) or root and rhizome biomass? 2) does grazing reduce non-structural carbohydrates? Overall, I observed root and rhizome biomass, root length, and starch (NSCs) were smaller in grazed treatment areas. All other root traits and non-structural carbohydrates were found to contrast between grazing treatments but varied in extent by location and soil depth. This investigation provides us a better understanding of how grazing can alter these belowground organs and reinforces the need for continued belowground ecological research, as changes in grassland belowground biomass and storage have the potential to negatively affect grass fitness and survival and grassland ecosystem services (e.g., carbon storage).
Keywords: Grazing; Drought; Grasslands; Root traitsGrass